Papaya Fruit (Carica papaya L.) and Its Effectiveness on Menstrual Patterns in Women Using Depo Medroxyprogesterone Acetate (DMPA): A Quasi-Experimental Study - Nurhayati Nurhayati; Suhermi Suhermi (Indonesian Socety of Obstetrics and Gynecology, 2026)
Objective: This study aims to determine the effectiveness of administering papaya ( Carica Papaya L) in Medroxy Depo Acceptor Progesterone Acetate (DMPA) on Menstrual Patterns in PMB Patmawati . Method: Research was conducted at PMB Fatmawati. This research is a Quasy-Experiment research with a Posttest Only Control Group Design research design where this research was carried out by providing treatment (intervention) in the form of Papaya fruit ( Carica Papaya L) then observing the Menstrual Cycle Pattern. Next, the measurement results were compared with the measurement results in the control group who did not receive treatment (intervention) consuming papaya fruit ( Carica Papaya L). Results: There was a significant effect between changes in menstrual patterns between groups that consumed papaya and those who did not consume papaya (p = 0.000) and thare was a significant difference before and after consuming papaya on changes in menstrual patterns (p=0.001). Conclusion: Consuming papaya fruit regularly and consistently ( carica Papaya L) as an acceptor of Medroxy Depo Progesterone Acetate (DMPA) shows a good effect on changing menstrual patterns from previously irregular to regular Keywords: DMPA, Papaya Fruit, Menstrual Cycle